Perspectives on the impact of the 3M national teaching fellowship program. Issue 4 (4th July 2017) - Smith, R.; Stockley, D.; Ahmad, A.; Hastings, A.; Kinderman, L.; Gauthier, L.
Abstract: The 3M National Teaching Fellowship (3MNTF) is the highest award in teaching in Canada and was first awarded in 1986, yet to date there has been no research measuring its impact on individual winners and their institutions. As part of this project, two focus groups were conducted at the 3MNTF Retreat in Banff, with the 2012 cohort, 3M retreat facilitators and coordinators and the representative from 3M Canada. In 2014, we conducted two additional focus groups with senior university administrators and educational developers at the Educational Developers Caucus Conference and a third focus group with the 2013 cohort at the Society for Teaching and Learning in Higher Education conference. This paper presents their perspectives on their unique set of experiences, both positive and negative, that reflect the impact of this award.